Diskursus Perkembangan Ilmu Syarah Hadith: Sebuah Kajian Metodologis dan Historis - Ahmad Nabil Amir (Program Studi Aqidah dan Filsafat Islam, 2021)
The study of the history of the development of hadith and ulumul hadith is one of the studies developed in Islamic science. This study is important because hadith is the second reference to Islam after the Qur'an. Therefore we need an in-depth study of the discourse on the development of